Gratitude and Quality of Life in Muslim Early Adulthood - Rahmania, Farra Anisa (Jurnal Psikologi Islam, 2020)
At the stage of development, individuals will pass the adolescence stage to the adult stage. At that stage, the individual will be in the early adult phase, where the individual will focus on preparing for his future and evaluating his adolescence so that in adulthood individuals have a quality life. In a quality life, there is an element of religiosity, wherein a Muslim's life gratitude is one aspect of religiosity. The objective of this study is to investigate the correlation between gratitude and quality of life in Muslim early adulthood. The subjects in this study were 101 Muslims early adulthood consisting of college students and working individuals. Data collection in this study uses a scale in the form of a questionnaire to reveal two variables, namely WHOQOL-BREF scale from WHO (World Health Organization) and then the scale of gratitude is a scale developed by Rusdi (2016). The results of data processing with Pearson Product Moment correlation on 101 subjects showed that quality of life and gratitude were positively correlated significantly (p <0.05) with p = 0.000 and the correlation coefficient of r = 0.450. The research had a limitation that the gratitude scale can only be applied to the subject of a Muslim because the measuring instrument used has a value that is trusted by Muslims and this research only applied to subjects in a number of regions in Indonesia. It is hoped that this research can be a study of psychology, especially in the study of Islamic psychology. Keywords: Gratitude, Quality of Life, Early Adulthood, Muslims